Cognitive Impairment Impacts Exercise Effects on Cognition in Multiple Sclerosis - Rademacher, Annette; Joisten, Niklas; Proschinger, Sebastian; Bloch, Wilhelm; Gonzenbach, Roman; Kool, Jan; Langdon, Dawn; Bansi, Jens; Zimmer, Philipp (Frontiers in Neurology, 2021)
Purpose: Exercise training reveals high potential to beneficially impact cognitive performance in persons with multiple sclerosis (pwMS). Research indicates that high-intensity interval training (HIIT) has potentially higher effects on physical fitness and cognition compared to moderate continuous exercise. This study (i) compares the effects of a 3-week HIIT and moderate continuous exercise training on cognitive performance and cardiorespiratory fitness of pwMS in an overall analysis and (ii) investigates potential effects based on baseline cognitive status in a subgroup analysis. Methods: Seventy-five pwMS were randomly assigned to an intervention (HIIT: 5 × 1.5-min intervals at 95–100% HRmax, 3 ×/week) or active control group (CG: 24 min continuous exercise at 65% HRmax, 3 ×/week). Cognitive performance was assessed pre- and post-intervention with the Brief International Cognitive Assessment for MS (BICAMS). (I) To examine potential within (time) and interaction (time × group) effects in the overall analysis, separate analyses of covariance (ANCOVA) were conducted. (II) For the subgroup analysis, participants were divided into two groups [intact cognition or impaired cognition (>1.5 standard deviation (SD) compared to healthy, age-matched norm data in at least one of the three tests of the BICAMS]. Potential impacts of cognitive status and intervention were investigated with multivariate analyses of variance (MANOVA). Results: Overall analysis revealed significant time effects for processing speed, verbal learning, rel. VO2peak, and rel. power output. A time*group interaction effect was observed for rel. power output. Subgroup analysis indicated a significant main effect for cognition (impaired cognition vs. intact cognition). Subsequent post-hoc analysis showed significant larger effects on verbal learning in pwMS with impaired cognition. Conclusion: Current results need to be confirmed in a powered randomized controlled trial with cognitive performance as primary endpoint and eligibility based on cognitive performance that is assessed prior to study inclusion.